Optimization Of The Force Characteristic Of Rotary Motion Type Of Electromagnetic Actuator Based On Finite Element Analysis - Yusri, Izzati; Md Ghazaly, Mariam; Ali Al-Andoli, Esmail Ali; Rahmat, Mohd Fua'ad; Zulkeflee, Abdullah; Md Ali, Mohd Amran; Ranom, Rahifa (Universiti Teknologi Malaysia, 2016)
-